Molecular interaction analyses of selected drugs as dengue virus type-2 protease inhibitors / Rufaidah Othman - Rufaidah , Othman (2017)
Dengue is a disease that is endemic to the tropical and subtropical regions of the world. It is a potentially deadly disease with no available effective drug. Thus, it is becoming increasingly important to develop therapeutics/drugs to combat the dengue virus. Compounds able to inhibit the NS2B-NS3 DENV-2 protease (NS2B-NS3pro) have potential anti-dengue activity. As such, we investigated several compounds that have previously been shown to inhibit the NS2B-NS3 protease of the dengue virus-2 (DENV-2). These compounds are antibiotic derivatives: doxycycline and rolitetracycline, and a non-steroidal anti-inflammatory drug (NSAID) - meclofenamic acid. Our focus was on the interaction between these compounds and NS2B-NS3pro where better interaction would suggest better inhibitory action. We used a combination of surface plasmon resonance (SPR) technology (Biacore 3000) and molecular docking simulations (Autodock 4.2.6). To the best of our knowledge, there are no studies investigating the molecular interactions of these inhibitors using a combination of these two approaches. In the initial part of the study, NS2B-NS3pro was expressed, and purified (to >90% purity) using Ni-IMAC and size exclusion chromatography (SEC). The protease complex was then bound to an NTA chip and interaction studies were performed. The resulting sensorgrams showed high reproducibility based on the overlaid replicates. However, the sensorgrams were not a fit to the 1:1 Langmuir model. The association phase showed significant deviation from pseudo-first order kinetic behavior. An attempt to fit to the heterogenous ligand-parallel reaction models was also unsuccessful. The Chi2 values were relatively optimal for doxycycline and meclofenamic acid (<10 RU), however, for rolitetracycline the values were beyond the limit value (>10 RU). Nevertheless, the residual values for all compounds were more than the optimal level of ± 2 RU. An in silico molecular docking approach was then performed. The results predicted that doxycycline to posses the highest binding affinity to the protease complex based on its binding energy of -5.15 kcal/mol followed by meclofenamic acid -3.64 kcal/mol and rolitetracycline -3.21 kcal/mol. It also suggested that doxycycline binds via a specific allosteric site involving interaction with Lys74, suggesting that it was a non-competitive inhibitor. On the other hand, meclofenamic acid and rolitetracycline was predicted to have a direct interaction with His51 and Ser135, suggesting that they were competitive inhibitors. In conclusion, this study has demonstrated the use of SPR and in silico approaches to study the potential interactions between drugs and its potential targets. The information obtained may eventually be used in the development of anti-dengue therapeutics.